Showman the life of David O. Selznick - Thomson, David 1941- (Knopf, 1992)
"This superb biography uncovers the private lives and business maneuverings of Hollywood as no other book has done. It chronicles the Golden Age as seen from deep inside the gold mine and from behind locked doors where the spoils were divided, filched, or gambled away. In its rich sense of the wonders, ironies, and delusions inherent in "showmanship," this is a book about America in this century, turning from reality toward the glamour, the legend - the fantasy - of the movies."--BOOK JACKET